Effect of adding fat to feedlot rations - Brent, B.E.; Phar, P.A.; Randle, L.J.; Harbers, L.H.; Allen, Dell M. (Kansas State University. Agricultural Experiment Station, 2011)
Fat is added to commercial feedlot rations as a concentrated energy source and to reduce dustiness and wear of feed processing machinery. We added fat at varying levels ( 0 to 6% of the ration) to study effects from fat and the influence of a surface-active additive. Two hundred 700-pound steers were allotted to 40 pens of 5 each all fed 135 days on the rations show in Table 12, according to the schedule shown in Table 13.
Keywords: Beef; Fat; Feedlot ration; Energy